1990
DOI: 10.1016/0014-5793(90)81066-w
|View full text |Cite
|
Sign up to set email alerts
|

Molecular cloning, nucleotide sequence and expression of the gene encoding prepro‐polygalacturonasell of Aspergillus niger

Abstract: Polygalact~ron~eIlof ~spergjtZ~ niger was fragmented using CNBr and the NHr-terminal fragment and another fragment were partially sequenced. The poiygalacturonasell @gofI) gene was then isolated by using an oligonucleotide mixture based on the internal ammo acid sequence as a probe. The nucleotide sequence of thepgaI1 structural gene was determined. It was found that polygalacturonaseI1 is synthesized as a precursor having an NH,-terminal prepro-sequence of 27 amino acids. The cloned gene was used to construct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
47
0

Year Published

1995
1995
2000
2000

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 81 publications
(49 citation statements)
references
References 18 publications
2
47
0
Order By: Relevance
“…The data clearly show that all four enzymes were able to hydrolyze the mixture. In addition to large amounts of GalpA, the products formed by all four enzymes were D4,5-unsaturated (GalpA) 2 and D4,5-unsaturated (GalpA) 3 and smaller amounts of (GalpA) 2 . In the case of endopolygalacturonase II, trace amounts of (GalpA) 3 were also detected.…”
Section: Hydrolysis Of D45-unsaturated Oligogalacturonatesmentioning
confidence: 99%
“…The data clearly show that all four enzymes were able to hydrolyze the mixture. In addition to large amounts of GalpA, the products formed by all four enzymes were D4,5-unsaturated (GalpA) 2 and D4,5-unsaturated (GalpA) 3 and smaller amounts of (GalpA) 2 . In the case of endopolygalacturonase II, trace amounts of (GalpA) 3 were also detected.…”
Section: Hydrolysis Of D45-unsaturated Oligogalacturonatesmentioning
confidence: 99%
“…Kexins have been cloned and characterized from yeasts and mammalian cells, and thus from an evolutionary perspective, the existence of such a function was predictable. The work done with polygalacturonases (6,7,8,23) and with fusion proteins that use engineered Kex2 sites at the fusion junction (reviewed in reference 13) suggested that this function exists in A. niger. The kexB gene we cloned encodes a Kex2-like dibasic endoprotease that has significant similarity to expressed sequence tags (ESTs) of two other filamentous fungi.…”
Section: Discussionmentioning
confidence: 99%
“…In these constructs, a consensus Kex2 cleavage site often separates the foreign protein from the endogenous protein. Studies with such fusion proteins in Aspergillus niger showed that amino acid residues directly adjacent to the cleavage site can affect correct processing of an engineered Kex2 site (30).Examples of physiological substrates for an A. niger kexinlike endoprotease are the endopolygalacturonase (Pga) family of proteins (6,7,8,23). They all contain a dibasic cleavage site at the carboxy-terminal end of their amino-terminal propeptide, except for PgaII, which has a single arginine residue preceding the cleavage site (6).…”
mentioning
confidence: 99%
See 2 more Smart Citations